The effects of self-efficacy on physical and cognitive performance: An analysis of meta-certainty. (January 2022) - Horcajo, Javier; Santos, David; Higuero, Guillermo
Abstract: In the present research, we analyzed the effects of self-efficacy (SE) on physical and cognitive performance in real-world settings as a function of the metacognitive certainty in SE. In three studies, participants completed a measure of SE, which asked them to report how sure they were that they can achieve several specific results on various athletic and academic tasks. Moreover, general certainty in their own SE (i.e., SEC) was measured (Studies 1 and 3) or manipulated to be high versus low (Study 2). Relevantly, our studies aimed to obtain a high level of ecological validity by including athletes in natural, real-world settings (i.e., gymnasiums). Furthermore, we sought to extend the findings beyond physical performance by analyzing university students' cognitive performance in their actual academic setting (i.e., classrooms). Specifically, physical performance was assessed with pull-ups (Study 1) and vertical jump tests (Study 2), and cognitive performance was measured with grades on exams (Study 3). As expected, SE was positively related to performance. Most importantly, we predicted and found an interaction between SE and SEC on performance. That is, the effect of SE on physical and cognitive performance was greater for participants with higher (vs. lower) metacognitive certainty in their SE. In conclusion, to increase the explanatory and predictive power of efficacy beliefs across different domains, we propose that the assessment of SE should also include measures of one's metacognitive certainty in SE. In addition, we suggest that interventions on SE could benefit from the use of certainty inductions when including these inductions is possible and convenient. Highlights: Self-efficacy had a greater impact on physical performance for participants with higher (vs. lower) metacognitive certainty. In addition, we extended our findings to cognitive performance in academic setting. These studies make a meaningful contribution because self-efficacy is a relevant construct in diverse domains of research. Future studies on self-efficacy could benefit from the use of metacognitive certainty measures to improve their predictions. Interventions on self-efficacy could benefit from the use of metacognitive certainty inductions to increase their effects.